Multi-Layered Diplomacy in a Global State - Holmes, Alison R. author. aut Link
XXIII, 234 p. 25 illus., 5 illus. in color.
Keywords: This book explores the growing importance of subnational diplomacy by examining the state of California. As the fifth largest economy in the world, California’s tribes, counties, cities and the state itself are changing the shape of diplomatic theory and practice and defining what it means to be a ‘global’ state. As both a theoretical text and a practical guide, this book offers a current snapshot of California, then connects this narrative to the fundamental international relations concepts of diplomacy and sovereignty and the working assumptions of professionals in the field. Through interviews with those representing all of the entities of the state - as well as the diplomats sent to the United States to represent the interests of their home countries - Holmes creates what she calls the ‘vertical axis of diplomacy’, providing context and depth to a (re)emerging form of diplomacy, increasingly relevant in this pandemic moment. Alison R. Holmes is Associate Professor and Program Leader for International Studies at Humboldt State University, USA. Prior to academe, Holmes worked in British politics for ten years, then in strategic communications for the BBC. She was also Managing Director for British-American Business and the US Ambassador’s speechwriter in London.